COVID 19 Pandemic and the Library Online Services: SSC Manila High School Librarians’ Experiences - Josiah Ramuel Narca (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The purpose of this study is to describe the experiences of St. Scholastica's College Manila High School librarians in implementing library online services during the COVID-19 Pandemic. The researcher used a descriptive research design and employed Document Analysis and Thematic Analysis vis-a-vis the respondents' answers on the electronic questionnaires. It was revealed, through this study, that the roles and responsibilities of the SSC Manila HS librarians were technologists, online learning support professionals, instructional partners, and game-based learning developers. On the other hand, they experienced challenges such as having limited transactions and time constraints in delivering library online services and the opportunities of having proactive team culture and providing appropriate and innovative services to their clientele. With these findings, the following are recommended for better library online services of the school libraries and librarians. First, librarians and staff's technical competencies and skills must continuously be honed. Second, the library's online services must also be evaluated annually by the students and faculty members. Third, the librarians and staff must explore more technological applications or apps and learning management systems. Lastly, further research studies are recommended in relation also to delivering library online services that can be in the contexts of other types of libraries, most especially their experiences so that there will be a deeper and bigger understanding of the roles and responsibilities, and the challenges and opportunities of librarians during the COVID-19 Pandemic.